(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The current research aims to identify the negotiation behavior of administrative teachers, as well as to identify the significance of the differences in negotiation behavior according to the variables (gender, scientific title, length of service). After confirming the psychometric characteristics of (20) items, the researchers applied the scale to (400) male and female administrative teaching staff who were randomly selected from the University of Baghdad for the academic year 2021/2022. The results showed the following the research sample has a negotiating behavior. There are no statistically significant differences between gender, scientific title, and length of service in the means of negotiating behavior.